2016
DOI: 10.1002/ldr.2522
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and Nitrogen Losses from Soil Depend on Degradation of Tibetan Kobresia Pastures

Abstract: Degradation of Kobresia pygmaea pastures has strongly increased on the Tibetan Plateau over the last few decades and contributed to a high loss of soil organic carbon and nutrients. The pathways of carbon (C) and nitrogen (N) losses from degraded K. pygmaea pastures are still unclear, but this is a prerequisite to assess the recovery of Tibetan grasslands. We investigated the response of day-and nighttime CO 2 efflux and leaching of dissolved organic C and N, NH 4 + and NO 3 -from K. pygmaea root mats in three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 69 publications
1
25
0
Order By: Relevance
“…Therefore, optimal N fertilizer for grain yield might be 300 kg ha −1 (Khaliq, 2008) with optimal irrigation water. Consequently, the application of higher doses of N with frequent water availability increases N leaching and has negative impacts on soil plant ecosystems (Liu, Schleuss, & Kuzyakov, 2017).…”
Section: Significant Interaction Between I and F Treatments Was Obsermentioning
confidence: 99%
“…Therefore, optimal N fertilizer for grain yield might be 300 kg ha −1 (Khaliq, 2008) with optimal irrigation water. Consequently, the application of higher doses of N with frequent water availability increases N leaching and has negative impacts on soil plant ecosystems (Liu, Schleuss, & Kuzyakov, 2017).…”
Section: Significant Interaction Between I and F Treatments Was Obsermentioning
confidence: 99%
“…These long-term degradation processes gradually shift the Kobresia pastures to dead root mats with lower C and N contents, microbial biomass and root biomass. Thus, the three root mat varieties sampled in our study represent the degradation continuum of Kobresia pastures (living < dying < dead, Liu et al, 2016).…”
Section: Sampling Preparation and Experimental Set-upmentioning
confidence: 99%
“…Six samples were randomly picked out from each root mat type and transferred to incubation boxes (Liu et al, 2016). The experiment was conducted at a constant temperature (20°C), which is in the range of daily mean temperatures during the growing season in Nagqu (9·3-21·3°C, Geng et al, 2012).…”
Section: Sampling Preparation and Experimental Set-upmentioning
confidence: 99%
“…According to some authors [6,9,10,12,18,22,27], soil's grazing intensity (under-and overgrazing) can lower carbon sequestration or lead to carbon losses. These authors observed efects of grazing mediated by changes in the removal, growth, carbon allocation and lora in pastures and carbon input from ruminant excreta, which afect the amount of carbon in soils [27,36,40].…”
Section: Introductionmentioning
confidence: 98%